Effect of sugar-based compounds in enhancing the efficacy of insecticides against the western flower thrips - Cloyd, Raymond A.; Gillespie, Joshua D. (My University, 2012)
It has been proposed by greenhouse producers that adding sugar to a stomach poison insecticide enhances the efficacy of the insecticide in controlling western flower thrips (Frankliniella occidentalis). As such, a series of laboratory, including no-choice and multiple-choice assays, and greenhouse experiments were conducted to determine if adding sugar-based compounds to insecticides enhances efficacy against western flower thrips. The sugar-based compounds evaluated were Mountain Dew, Diet Mountain Dew, white sugar, and brown sugar at two rates [initial (0.18 mL/100 mL and 0.12 g/100 mL) and high (0.36 mL/100 mL and 0.24 g/100 mL)]. A water control was also included in all the assays. In the laboratory experiments, western flower thrips adults and nymphs were not attracted to any of the sugar-based compounds with <60 s (out of 300 s total) spent in any of the treatments, and ≤29 s (out of 300 s total) spent in the treatments when the sugar-based compounds were mixed with three insecticides (tau-fluvalinate, pyridalyl, and spinosad). In the greenhouse experiments, the addition of the high rate of Mountain Dew (0.36 mL/100 mL) and brown sugar (0.24 g/100 mL) did not enhance the efficacy (based on percent mortality) of the insecticides against western flower thrips. There was no significant difference between the individual insecticide treatments and the mixtures with either Mountain Dew or brown sugar. This study is the first to quantitatively demonstrate that western flower thrips adults and nymphs are not attracted to sugar-based compounds and that it is not warranted to add these types of materials to spray solutions targeted for control of western flower thrips.
Citation: Cloyd, R., & GIllespie, J. (2012). Effect of Sugar-based Compounds in Enhancing the Efficacy of Insecticides against the Western Flower Thrips. HortTechnology, 22(2), 177-184. https://doi.org/10.21273/HORTTECH.22.2.177
Keywords: Frankliniella occidentalis; Sugar enhancement; Pesticide efficacy; Pesticide additives; Floriculture; Pest management; Western flower thrips; Sugar-based compounds